(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article emphasizes that the basis for the identification of directions of ensuring public safety and order by the police is their understanding within the framework of a broad system, the smooth functioning of which requires the implementation of a wide range of technical, informational and other measures, the totality of which, provided that it is aimed at solving a specific problem issue, constitutes a direction of provision. It is determined that special attention should be paid to proper control during the direct provision of public safety and order services. Such control is primarily entrusted to the heads of district police departments (departments), their deputies for preventive activities, and persons who perform their duties. The personal presence of this category of leaders is important both at briefings and during the events themselves. The direction of ensuring public order during mass gatherings of citizens is considered. In the context of this direction, it is noted that it is important to cultivate in Ukrainian society a special culture of behavior in places where citizens gather. It is emphasized that in situations of high social tension, the ability of the police to direct aggression or conflicting moods of significant groups of citizens in a constructive direction depends on effective communication.